Parenting and Children's Moral Values in the Gadget Era: A Rural Ethnographic Study - Lety Febriana; Desi Firmasari; Syukri Amin (Yayasan Darusssalam Bengkulu, 2026)
The development of digital technology has influenced parenting patterns and the process of moral value formation within families. The increasing use of gadgets by children poses new challenges for parents in maintaining the process of moral value internalisation. This study aims to understand the dynamics of parenting in instilling moral values in children amid the use of gadgets in Talang Donok Village. The study uses a qualitative approach with ethnographic methods to explore parenting practices, social interactions, and community experiences in everyday life. Data was obtained through participant observation, in-depth interviews with parents, children, community leaders, and religious leaders, as well as documentation of the community's social and religious activities. The results of the study show that the family remains the primary environment in the process of internalising moral values through strategies such as giving advice, instilling positive behaviour, parental role modelling, and supervising gadget use. In addition, the social environment and religious activities of the community also play a role in strengthening the character building of children. However, the increasing use of gadgets in some cases reduces children's involvement in social and religious activities. Therefore, the active role of families and communities is needed in directing the use of digital technology so that it remains in line with the formation of moral values in children.